Professional Knowledge and Self-Efficacy Expectations of Pre-Service Teachers Regarding Scientific Reasoning and Diagnostics - Dagmar Hilfert-Rüppell; Monique Meier; Daniel Horn; Kerstin Höner (MDPI AG, 2021)
Understanding and knowledge of scientific reasoning skills is a key ability of pre-service teachers. In a written survey (open response format), biology and chemistry pre-service teachers (n = 51) from two German universities claimed central decisions or actions school students have to perform in scientific reasoning in the open inquiry instruction of an experiment. The participants' answers were assessed in a quality content analysis using a rubric system generated from a theoretical background. Instruments in a closed response format were used to measure attitudes towards the importance of diagnostics in teacher training and the domain-specific expectations of self-efficacy. The pre-service teacher lacked pedagogical (didactics) content knowledge about potential student difficulties and also exhibited a low level of content methodological (procedural) knowledge. There was no correlation between the knowledge of student difficulties and the approach to experimenting with expectations of self-efficacy for diagnosing student abilities regarding scientific reasoning. Self-efficacy expectations concerning their own abilities to successfully cope with general and experimental diagnostic activities were significantly lower than the attitude towards the importance of diagnostics in teacher training. The results are discussed with regard to practical implications as they imply that scientific reasoning should be promoted in university courses, emphasising the importance of understanding the science-specific procedures (knowing how) and epistemic constructs in scientific reasoning (knowing why).